ETIKA SOSIAL KRISTEN SEBAGAI RESPONS TEOLOGIS TERHADAP KRISIS MORALITAS DIGITAL: TANTANGAN PEMBENTUKAN KARAKTER GENERASI MUDA GEREJA DI ERA MEDIA SOSIAL - Inra Patuju (Adisam Publisher, 2026)
The digital era has brought fundamental changes in social interaction patterns and moral formation, particularly among the younger generation of the church. This study aims to formulate Christian social ethics as a theological response to the digital morality crisis in the context of character formation for the younger church generation. Using a qualitative research method based on library research with a theological-conceptual approach, this study analyzes various digital moral crisis phenomena such as cyberbullying, hoax dissemination, and dehumanization in online communication. The findings show that Christian social ethics rooted in the principles of agape, imitatio Christi, and Kingdom ethics can serve as a contextual theological foundation for shaping the digital character of the younger church generation. The church is called to be actively present as an agent of moral transformation in the digital space through contextual discipleship, cross-institutional collaboration, and faith-based digital literacy development. This research contributes to the development of applied Christian ethics relevant to the digital reality of today's younger church generation.